Cellular response to chemicals present in air pollution in occupationally exposed workers and its potential cancer susceptibility. (January 2021) - Gauer, Bruna; Sauer, Elisa; Nascimento, Sabrina; Göethel, Gabriela; Peruzzi, Caroline; Flesch, Ingrid; Fão, Nuryan; Cestonaro, Larissa; Sant'Pierre, Tatiana; Gioda, Adriana; Matte, Ursula; Brucker, Natália; et al.
Abstract: The study aimed to evaluate the potential effects of the chronic exposure to chemical agents from air pollution on phenotypic and genotypic expressions of peripheral biomarkers and tumor-related proteins in mononuclear cells. This study evaluates 85 taxi drivers (outdoor workers) and 55 non-occupationally exposed persons (NOE) to air pollution (indoor workers). The biomarkers were urinary 1-hydroxypyrene (1-OHP), for organic agents, and blood As and Ni, for inorganic agents. Oxidative stress biomarkers; protein expression of ICAM-1 (CD54), β2-integrin, L-selectin (CD62-L), and MCP1; gene expression of ICAM-1, p53 and CD26 were performed. Urinary 1-OHP and blood As and Ni levels were increased in taxi drivers and were associated with inflammatory and oxidative stress biomarkers. These exposure biomarkers were also associated with each other, suggesting a common source of exposure. The gene expression of p53, CD26 and ICAM-1 were decreased in taxi drivers and were strongly associated between them, indicating a commom regulation point. The antioxidant non-protein thiols and lycopene were negatively associated with inflammatory biomarkers, maybe regulating the immune-response. We demonstrated, for the first time, that in occupational exposure to air pollution chemicals, oxidative and inflammatory processes are involved in the immune-regulatory process, and indirectly contribute to suppressing the p53 and CD26 expressions, increasing the risk of cancer development. On the other hand, antioxidants could contribute to improving the immune-regulation, but more studies are needed. Graphical abstract: Image 1 Highlights: Workers chronically exposed to pyrenes, arsenic and nickel, in high levels, demonstrated impair the immune-regulation. Oxidative stress and inflammation are involved in the immune-regulatory process in taxi drivers, in a negative manner. Suppression of p53 and CD26 expression is a possible risk to cancer in taxi drivers. Exogenous antioxidants, as lycopene, may contribute positively to the immune-regulation.